Integrating Smart Decarceration Content Across Social Work Curricula. (2nd January 2023) - Young, Diane S.; Trawver, Kathi R.; Harris, Abril N.; Jacob, Daniel
ABSTRACT: Given tremendous negative societal effects of mass incarceration, the social work profession's investment in the Grand Challenge to Promote Smart Decarceration, and the call for criminal justice transformation, educational content that prepares social work students to engage in smart decarceration efforts is essential. This article presents strategies for integrating content on smart decarceration into courses across the social work curriculum, including human behavior in the social environment, practice, policy, research, and field education. Suggestions are included that address competencies on ethics, diversity, and justice. Rationale is provided for an integrated curricular approach and guiding principles are put forward. Equipping social work educators to prepare graduates to participate in smart decarceration efforts benefits the individuals and communities that the profession serves.